Design of novel titanium-copper alloys for dental implant applications - Mavundla Muzi; Cornish Lesley (MATEC Web of Conferences)
Although the main alloy used in dentistry is Ti-6Al-4V, there are concerns of toxicity with Al and V, as well as bacterial infections after implantation. Novel Ti-Ta-Mo-Sn- xCu ( x = 0, 5 (wt%)) compositions were derived using Thermo-Calc® and manufactured using a button arc furnace. Addition of 5 wt% Cu produced Ti2Cu, linked to potentially improved antibacterial properties. SEM-EDX was used to determine the compositions and microstructures, XRD for phase identification, potentiodynamic polarisation test to investigate corrosion behaviour and hardness test to measure resistance to indentation.